AS AN EXAMPLE OF FOREIGN EXPERIENCES ON TECHNOLOGIES OF WORKING WITH YOUNG PEOPLE IN HIGHER EDUCATION (American Journal of Research in Humanities and Social Sciences, 2024)
Technologies for working with young people are important in the higher education system. They serve not only to effectively organize the educational process, but also to ensure social and cultural development among students. Foreign experiences provide interesting examples in this regard.